A Kink that Makes you Sick: the Effect of Sick Pay on Absence in a Social Insurance System - Petri Bockerman; Ohto Kanninen; Ilpo Suoniemi (Aboa Centre for Economics (ACE), 2014)
We examine the effect of the replacement rule of a social insurance system on sickness absence. The elasticity of absence with respect to the benefit level is a critical parameter in defining the optimal sickness insurance scheme. A pre-determined, piecewise linear policy rule in which the replacement rate is determined by past earnings allows identification of the causal effect using a regression kink design. Using a large administrative dataset, we find a substantial and robust behavioral response. The statistically significant point estimate of the elasticity of the duration of sickness absence with respect to the replacement rate in a social insurance system is on the order of 1.
Keywords: C72; C73; 330; Sick pay; labor supply; sickness absence; paid sick leave; regression kink design